Concise handbook of civil engineering - VAZIRANI, V.N (S. Chand & Company LTD, 2002)
This 'Concise Handbook'has been prepared,keeping in view mainly the requirements of practising Civil Engineers,with all the essential of a useful'Concise Handbook'.such as the latest design formulae,graphs,diagrams and tables etc.,to solve day-to-day work problems.These details have been adopted mostly from the national building code.The book will be equally helpful to civil Engineering students and teachers.